Fishery, biology and stock structure of skipjack tuna, Katsuwonus pelamis (Linnaeus, 1758) exploited from Indian waters - K P Said, Koya (Indian Journal of Fisheries, 2012)
Fishery and population dynamics of skipjack tuna, Katsuwonus pelamis (Linnaeus), was studied during the period 2006-2010. Length frequency data from gillnet as well as pole and line catches were used for estimation of the growth parameter using FiSAT software. Total landing showed substantial increase from 5,882 t in 1985-’89 to 20,924 t in 2006-â€™10. However, since 2007, the landings exhibited a continuous decline. Replica pattern reported by some of the adjacent tuna fishing nations call for a cautious approach. Exploited size of the species ranged from 12 to 88 cm fork length (FL). On an average, 31.7% landings of skipjack was contributed by Island systems, 31.4% by south-east coast, 23.2% by north-west coast, 12.3% by south-west coast and 1.3% by north-east coast. Among the maritime states and island territories, the major contributors were Lakshadweep (29.9%), Andhra Pradesh (18.3%), Gujarat (13.2%), Tamil Nadu (12.8%), Kerala (10.2%), Karnataka (2.08%) and the rest by Orissa, West Bengal, Puducherry and Andaman and Nicobar Islands. The species mature and spawn round the year with peak during December- March. Fecundity estimated was 3, 00,718 per kg body weight. Recruitment to the fishery takes place during most part of the year with peak during May-November. Length-weight relationship was W=0.0109 L3.147. The von Bertalanffy growth factors (VBGF) were Lâˆ = 92.0 cm, K=0.50 yr-1 and to= -0.0012. Estimate of total mortality (Z) was 1.41, natural mortality (M) 0.557, fishing mortality (F) 0.853 and exploitation rate (E) 0.605. This indicates moderate fishing pressure on the stock in the present fishing grounds. Presently fishing is centered at selected grounds and stocks at many areas like shelf break areas, reefs, banks, seamounts and Andaman waters remain largely under low fishing pressure. Scope for increasing the production from the present grounds is limited and hence the scope for enhancing production from the hitherto under-exploited grounds may be explored. There is an urgent need for international co-operation among Indian Ocean tuna fishing nations for optimum exploitation and sustainable management of the stock.